Plant Virology Protocols From Virus Isolation to Transgenic Resistance - Foster, Gary D.; Foster, Gary D.; Taylor, Sally.; Taylor, Sally. (Methods in Molecular Biology, 1998)
Plant Virology Protocols offers for the first time a comprehensive collection of state-of-the-art techniques for generating transgenic plants that are resistant to plant viruses via the cloning and expression of the coat protein gene. Its unfailingly reproducible methods, perfected by hands-on masters, cover the entire process from virus isolation, RNA extraction, and cloning coat protein genes, to the introduction of the coat protein gene into the plant genome and the testing of transgenic plants for resistance. Methods for testing for transformation by PCR and Southern blotting, the detection of RNA transcripts by Northern blotting, and the production of protein by Western analysis are provided, as are methods for challenging the transgenic plants produced and for detecting and measuring the levels of virus. The authoritative contributors also discuss the history and mechanisms of coat protein-mediated protection and the key ethical issues surrounding transgenic technology. Unprecedented in its comprehensiveness and its many time-proven methods, Plant Virology Protocols is certain to become the authoritative standard reference for plant scientists who want to tap the enormous benefits this technology has to offer.